Research of an Improved Trajectory Planning Method for Industrial Robot - Qingbo Kong; Liang Yuan; Wei Jiang (Jixie chuandong)
An improved quintic polynomial interpolation method is proposed to solve the catastrophe phenomenon caused by the original method order in the course of solving the motion trajectory of the robot. The ER 3A-C60 industrial robot produced by a company is taken as the research object. Using the standard D-H parameter method， the coordinate system of the robot connecting rod is established first， then， the robot simulation model is created and the kinematics forward solution and inverse solution are solved， the workspace point cloud image at the end of the robot is also been made. In the process of solving robot motion trajectory， a fusion method of polynomial interpolation and B-spline interpolation is proposed to eliminate the catastrophe phenomenon. The experimental results show that the optimized joint correlation curve is smoother， the mutation phenomenon is eliminated， and the impact of vibration and shock on the performance and life of the robot is avoided.